The Relevance of the Marriage Age Maturation Program according to Law No. 52/2009 from the Perspective of Maqāṣid al-Syarī'ah (Case Study in Bontoa District, Maros Regency) - Alimahmudrikah, Nur; Muh. Bakry, Muammar; Asni; Nazaruddin (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2024)
The purpose of this study is to reveal the relevance of the Marriage Age Maturation Program according to Law No. 52 of 2009 from the perspective of Maqāṣid al-Syarī'ah in Bontoa District, Maros. This research is qualitative research, the type of research is field research. The data collection methods used in this research are observation, interview and documentation. Data processing and data analysis techniques used through three stages, namely: data reduction, data presentation, data verification, data classification, data analysis and conclusion drawing. The results showed that; the relevance of Maqāṣhid al-Syarī'ah to the implementation of the Marriage Age Advancement Program according to Law No. 52 of 2009 in Bontoa District, Maros Regency is in expectation of improving the quality and controlling the quantity of the population, the five main elements in Maqāṣhid al-Syarī'ah are very relevant to the Marriage Age Advancement Program for the sake of benefit and preventing evil.